2017
DOI: 10.1038/s41598-017-12749-x
|View full text |Cite
|
Sign up to set email alerts
|

Pore formation in lipid membrane II: Energy landscape under external stress

Abstract: Lipid membranes are extremely stable envelopes allowing cells to survive in various environments and to maintain desired internal composition. Membrane permeation through formation of transversal pores requires substantial external stress. Practically, pores are usually formed by application of lateral tension or transmembrane voltage. Using the same approach as was used for obtaining continuous trajectory of pore formation in the stress-less membrane in the previous article, we now consider the process of por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 46 publications
(110 reference statements)
8
86
1
Order By: Relevance
“…The difference between DC‐glycerol and DC‐MTS can be explained by considering the lipid molecules as flexible chains and the intermolecular bonds due to reticulation as consolidating structures. In DC‐glycerol‐R, the upper part (above the reticulation bonds) of the lipid layer can splay under the electric field, hence creating opened and disorganized regions with reduced insulating performances. It was indeed shown that for self‐assembled monolayers of long alkyl chains the leakage current density varies drastically with the chain length (for small chain length it is mainly due to electron tunneling through the layer) as well as with the compacity and ordering of the layer .…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The difference between DC‐glycerol and DC‐MTS can be explained by considering the lipid molecules as flexible chains and the intermolecular bonds due to reticulation as consolidating structures. In DC‐glycerol‐R, the upper part (above the reticulation bonds) of the lipid layer can splay under the electric field, hence creating opened and disorganized regions with reduced insulating performances. It was indeed shown that for self‐assembled monolayers of long alkyl chains the leakage current density varies drastically with the chain length (for small chain length it is mainly due to electron tunneling through the layer) as well as with the compacity and ordering of the layer .…”
Section: Resultssupporting
confidence: 77%
“…Both mechanisms have been studied theoretically in water for nonreticulated supported lipid layers or cell membranes . In the framework of nanoindentation experiments, Butt and co‐workers developed a two‐state film rupture reaction theory based on the assumption that an AFM tip can rupture the lipid layer after the formation of a sufficiently large hole under the tip.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explain the mechanism of the line activity, a concept of so-called hybrid lipids was proposed 28 : in order to be line-active, hybrid lipids www.nature.com/scientificreports www.nature.com/scientificreports/ calculated up to the second order in deformations, which are assumed to be small. In a quadratic approximation, the elastic energy of the monolayer can be expressed as 40,45,46 : Scientific RepoRtS | (2020) 10:4087 | https://doi.…”
mentioning
confidence: 99%